2018
DOI: 10.1073/pnas.1718206115
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral correlates of obesity are largely heritable

Abstract: SignificanceObesity is a widespread heritable health condition. Evidence from psychology, cognitive neuroscience, and genetics has proposed links between obesity and the brain. The current study tested whether the heritable variance in body mass index (BMI) is explained by brain and behavioral factors in a large brain imaging cohort that included multiple related individuals. We found that the heritable variance in BMI had genetic correlations 0.25–0.45 with cognitive tests, cortical thickness, and regional br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
118
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(139 citation statements)
references
References 53 publications
19
118
2
Order By: Relevance
“…Given that losing weight is a difficult task, the Conscientiousness facets may reflect troubles with adherence to weight loss regimens in people with obesity. The importance of planning and organizing tasks conceptually supports the role that self‐control plays in obesity, which has also been highlighted by research on executive functions and prefrontal cortex . Scarce longitudinal evidence has suggested that obesity could have bidirectional associations with self‐control capabilities, while a Mendelian randomization study suggested that higher education and cognitive ability could cause lower BMI …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that losing weight is a difficult task, the Conscientiousness facets may reflect troubles with adherence to weight loss regimens in people with obesity. The importance of planning and organizing tasks conceptually supports the role that self‐control plays in obesity, which has also been highlighted by research on executive functions and prefrontal cortex . Scarce longitudinal evidence has suggested that obesity could have bidirectional associations with self‐control capabilities, while a Mendelian randomization study suggested that higher education and cognitive ability could cause lower BMI …”
Section: Discussionmentioning
confidence: 99%
“…These weighted NEO PI‐R/3 (a) domain and (b) facet scores were then averaged, yielding either DRS or FRS. We included all NEO PI‐R/3 domains in DRS and all facets in FRS regardless of the magnitude or significance of their respective meta‐analytic weights, as many papers working on polygenic risk scores have shown that the best prediction can generally be achieved when all predictors are included in risk scores, no matter the effect size . The observed BMI was then predicted from the DRS and FRS (all expressed in z scores), controlling for sex, age, age 2 , and education.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity is the result of a sustained excessive energy intake (Hall, ), and energy intake is 100% accounted by behaviour (Blundell & Finlayson, ). Furthermore, evidence from genetics and brain imaging suggest that obesity's causes are rooted in the brain (Dagher, ; Vainik et al ., , ; Locke et al ., ). Therefore, individual differences in obesity should at least partly be explained by individual differences in behaviour.…”
Section: Introductionmentioning
confidence: 99%